Be rich overnight or remain poor for life on the sea's bounty - Roxas, Alita T.; Poblete, Teresita O.; Gomez, Aurelia Luzviminda V. (2007)
This paper presents results of a study in resource utilization and livelihood strategies in Barangay Taboc Norte and Taboc Sur in Oroquieta City, Misamis Occidental conducted under the Philippines-Neatherlands Biodiversity Research Programme (BRP) for Development in Mindanao, focus on Mt. Malindang and its Environs. Drawing data from a survey of sample fisher households and from qualitative research methods as key informant interviews, focus group discussions, and direct observation, the paper shows certain dynamics in people-environment interactions. It assess how access to and ownership of certain assets - as mediated by gender and class - enable households to translate them into livelihood strategies. The paper likewise discusses the influence of the asset status of the fisher households and the fishers' awareness of the Philippine Fisheries Code on livelihood security and environmental sustainability and gives recommendations that focus on addressing asset poverty and co-managing coastal resources.
Keywords: Resource utilization; Livelihood security; Terrestrial ecosystems; Coastal ecosystem management; Mindanao studies